Classification of Erythrina provenances by rumen degradation characteristics of dry matter and nitrogen - Larbi, Asamoah; Kurdi, I.O.; Said, A.N.; Hanson, Jean (Springer, 1996)
Some species of the genus Erythrina have considerable potential as forage, but information on their nutritional value is scanty. The objective of the study was to define groups of Erythrina provenances based on rumen degradation parameters for dry matter and nitrogen which would be useful in the selection of provenances for detailed nutritional or tree improvement studies. Degradation parameters (i.e. soluble fraction (a), slowly degradable fraction (b) rate of degradation (c) and extent of degradation (a+b) were estimated for twenty Erythrina provenances beloging to seven species (E. abyssinica, E. bentipoeme, E. brucei, E. burana, E. melanacantha, E. poeppigiana and E. variegata)). The data were subjected to principal component and cluster analyses for grouping, and the 20 provenances were placed into four distinct cluster groups. Provenances of E. brucei and E. abyssinica belonged to three clusters, whereas provenances of E. burana and E. variegata were confined to one cluster. Using extent of dry matter and nitrogen degradation values of 71 and 86 percent respectively, as a forage quality index, members of clusters 1 and 2 (i.e. E. abyssinica, ILCA 10606; E. brucei, ILCA 10579, 10625, 10628, 10637, 10643; E. burana 10575, 10641, 12157; E. melanacantha ILCA 10574 and E. variegata ILCA 14991 and 14994), appeared to be superior in quality to their counterparts in clusters 3 and 4. The results suggested existence of intra and inter-species variation in rumen degradation characteristics for dry matter and nitrogen within the genus Erythrina.